Cost effectiveness of regorafenib as second‐line therapy for patients with advanced hepatocellular carcinoma. Issue 19 (29th June 2017) - Parikh, Neehar D.; Singal, Amit G.; Hutton, David W.
Abstract : BACKGROUND: Regorafenib, a multikinase inhibitor, has demonstrated prolonged survival by 2.8 months as a second‐line agent in patients with hepatocellular carcinoma (HCC) who progress on sorafenib therapy. The objective of the current study was to examine the cost effectiveness of regorafenib for the treatment of HCC. METHODS: The authors constructed a Markov simulation model of patients with unresectable HCC and Child‐Pugh A cirrhosis who received treatment with regorafenib versus best supportive care. Model inputs for regorafenib effectiveness and rates of adverse events in patients with HCC were based on published clinical trial data and literature review. Quality‐adjusted life years (QALYs) were calculated along with the incremental cost‐effectiveness ratio (ICER) of regorafenib therapy. One‐way sensitivity analyses also were conducted simultaneously on all model parameters and on various Monte‐Carlo simulation parameters, and the regorafenib cost threshold at which cost effectiveness would be achieved was determined. RESULTS: Regorafenib provided an increase of 0.18 QALYs at a cost of 47, 112. The ICER for regorafenib, compared with best supportive care, was 224, 362. In 1‐way sensitivity analyses, there were no scenarios in which regorafenib was cost effective. In cost threshold analysis, regorafenib would have to be priced at or below 67 per pill to be cost effective at an ICER of 100, 000. CONCLUSIONS: Regorafenib is not cost effective as a second‐line agent in the treatment of HCC, with a marginal increase in QALYs at a high cost. Lowering the cost of regorafenib or improving the selection of patients who can achieve maximal survival benefit would improve its value as a second‐line treatment option for patients with HCC. Cancer 2017;123:3725–3731. © 2017 American Cancer Society Abstract : Regorafenib confers a survival benefit as a second‐line, systemic treatment for advanced hepatocellular carcinoma. The current study examines the cost effectiveness of regorafenib in this setting. See also pages 000‐000.